Steatosis and steatohepatitis in postmortem material from Northwestern Greece - Zois, Christos D (The WJG Press and Baishideng, 2010)
AIM: To determine the prevalence of steatosis and steatohepatitis in a series of autopsies in Northwestern Greece. METHODS: Liver biopsy material from a total of 600 autopsies performed over a period of 2 years (2006-2008) to define the cause of death was subjected to histological examination. Patient demographic data were also collected. Tissue sections were stained with different dyes for the evaluation of liver architecture, degree of fibrosis and other pathological conditions when necessary. RESULTS: Satisfactory tissue samples for histological evaluation were available in 498 cases (341 male, 157 female) with a mean age of 64.51 ± 17.78 years. In total, 144 (28.9%) had normal liver histology, 156 (31.3%) had evidence of steatosis, and 198 (39.8%) had typical histological findings of steatohepatitis. The most common causes of death were ischemic heart disease with or without myocardial infarction (43.4%), and traffic accidents (13.4%). CONCLUSION: A high prevalence of steatosis and steatohepatitis was detected in postmortem biopsies from Northwestern Greece. Since both diseases can have serious clinical consequences, they should be considered as an important threat to the health of the general population in Greece.